2018
DOI: 10.1038/s41409-018-0403-2
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective comparison of allogenic and autologous chimeric antigen receptor T cell therapy targeting CD19 in patients with relapsed/refractory acute lymphoblastic leukemia

Abstract: The source of CAR T cells can be autologous (autoCAR) or allogeneic (alloCAR). The latter is seen in patients with a history of allogeneic hematopoietic stem cell transplantation, and can be either donor-derived (DD-alloCAR) or recipientderived (RD-alloCAR). While autoCAR is activated by CAR only, alloCAR receives activation signals from both T-cell receptor (TCR) and CAR. As a result, the biological differences could impact clinical outcomes. We retrospectively reviewed 31 patients: 17 received autoCAR, 11 re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 32 publications
2
38
0
Order By: Relevance
“…Fifteen patients in our cohort had previous allogeneic HCT, 3 of whom among them three (20%) developed GVHD requiring systemic immunosuppressive therapy after CAR-T cell therapy. Similarly, Hu et al [28] reported acute GVHD in 2 out of 11 patients (18%) who received CAR-T cells after previous allogeneic HCT. This is not an unexpected rate of GVHD during this period after transplantation [29], suggesting that the risk of exacerbation of GVHD is not markedly increased after CAR-T cell therapy.…”
Section: Discussionmentioning
confidence: 79%
“…Fifteen patients in our cohort had previous allogeneic HCT, 3 of whom among them three (20%) developed GVHD requiring systemic immunosuppressive therapy after CAR-T cell therapy. Similarly, Hu et al [28] reported acute GVHD in 2 out of 11 patients (18%) who received CAR-T cells after previous allogeneic HCT. This is not an unexpected rate of GVHD during this period after transplantation [29], suggesting that the risk of exacerbation of GVHD is not markedly increased after CAR-T cell therapy.…”
Section: Discussionmentioning
confidence: 79%
“…CAR T cells targeting CD19 are, to date, the best studied and have demonstrated significant activity in chemotherapy refractory CLL, B-cell lymphomas and B-ALL in the autologous setting (103)(104)(105)(106)(107)(108). There is also growing evidence of the efficacy of donor-origin CD19 CAR T cells in patients relapsing after allo-HCT (102,(108)(109)(110)(111) or even haplo-HCT (112,113). In this scenario, the infusion of allogeneic CAR T cells could carry the theoretical risk of GvHD; however, incidence of this fearsome complication in early trials was quite low, and an elegant study in mouse models showed that the CAR-driven and TCR-driven signal actually adds up, accelerating exhaustion and limiting alloreactions (101).…”
Section: Adoptive Immunotherapy With Genetically Redirected Immune Cellsmentioning
confidence: 99%
“…In this scenario, the infusion of allogeneic CAR T cells could carry the theoretical risk of GvHD; however, incidence of this fearsome complication in early trials was quite low, and an elegant study in mouse models showed that the CAR-driven and TCR-driven signal actually adds up, accelerating exhaustion and limiting alloreactions (101). Still, a number of studies are focusing on the development of improved strategies to further enhance CAR T efficacy and persistence without risking to induce GvHD, such as by transducing recipient-derived donor T cells (113), by using genome editing approaches to knock out the endogenous TCR (101, 114), or by modifying with the CAR different immune cells, less prone to induce GvHD (85,115,116).…”
Section: Adoptive Immunotherapy With Genetically Redirected Immune Cellsmentioning
confidence: 99%
“…In this study, recipient-derived CAR-T cell therapy showed an increased complete remission (CR) rate with less severe CRS patients than autologous CAR-T cell therapy. Even though recipient-derived CAR-T cells are not truly allogeneic, this study reveals the potential therapeutic effect of allogeneic CAR-T cells therapy for patients with relapsed/refractory ALL [42]. Meanwhile, post allogeneic HSCT was tried after CAR-T cell therapy for patients with ALL, NHL (B-cell non-Hodgkin lymphoma), and CLL (chronic lymphocytic leukemia) to evaluate posttransplant toxicities.…”
Section: Effectiveness Of Allogeneic Car-t Cell Therapymentioning
confidence: 99%